Revitalisasi Tindak Pastoral Gereja: Sebuah Kajian Teologis Pastoral - Agut, Yoseph Selvinus (Jurnal Teologi Berita Hidup, 2025)
The article is a theological-pastoral overview of the Church's pastoral methods and actions. This article is a qualitative research with a literature study approach related to pastoral ideas and actions in the Church. It is important to emphasize that pastoral action is the Church's response to various needs, both problems and hopes, among the faithful. Revitalising pastoral actions should begin with an adequate understanding of the basic principles of pastoral action and the constitutive elements that support it. It is realised that many pastoral ideas and actions need to be interpreted and re-evaluated (revitalisation) in order to attain the aim of pastoral action, that is the salvation of the faithful. A good and right pastoral action always departs from a correct understanding of the dynamics of people's lives, knows the context of their lives, and has a sense that is in harmony with their wishes. The signs of the times require the Church to have a reflective attitude that is relevant and contextualised critically, which leads to the renewal of its pastoral actions. Reflective evaluation (revitalisation) of every pastoral action becomes the key point of whether the Church really wants to become more relevant and contextualized.